Molecular Biology - Howell, Stephen H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
In this book, plant biology is considered from the perspective of plants and their surrounding environment, including both biotic and abiotic interactions. The intended audience is undergraduate students in the middle or final phases of their programs of study. Topics are developed to provide a rudimentary understanding of how plant-environment interactions span multiple spatiotemporal scales, and how this rudimentary knowledge can be applied to understand the causes of ecosystem vulnerabilities in the face of global climate change and expansion of natural resource use by human societies. In all chapters connections are made from smaller to larger scales of ecological organization, providing a foundation for understanding plant ecology. Where relevant, environmental threats to ecological systems are identified and future research needs are discussed. As future generations take on the responsibility for managing ecosystem goods and services, one of the most effective resources that can be passed on is accumulated knowledge of how organisms, populations, species, communities and ecosystems function and interact across scales of organization. Molecular Biology is intended to provide some of that knowledge, and hopefully provide those generations with the ability to avoid some of the catastrophic environmental mistakes that prior generations have made.
Control of transcription (incl miRNA) -- Control of translation -- Macromolecular structures (carbohydrates, proteins etc) -- Enzyme function and enzyme-enzyme interactions -- Photosynthesis -- Primary metabolism -- Natural products chemistry (secondary metabolism) -- Proteomics -- Metabolomics -- Synthetic biology.
Keywords: Life sciences; Plant biochemistry; Plant science; Botany; Plant anatomy; Plant development; Plant genetics; Plant pathology; Life Sciences; Plant Genetics & Genomics; Plant Biochemistry; Plant Sciences; Plant Anatomy/Development.; Plant Pathology; Electronic books